2007
DOI: 10.1158/1535-7163.mct-07-0202
|View full text |Cite
|
Sign up to set email alerts
|

A new class of anticancer alkylphospholipids uses lipid rafts as membrane gateways to induce apoptosis in lymphoma cells

Abstract: Single-chain alkylphospholipids, unlike conventional chemotherapeutic drugs, act on cell membranes to induce apoptosis in tumor cells. We tested four different alkylphospholipids, i.e., edelfosine, perifosine, erucylphosphocholine, and compound D-21805, as inducers of apoptosis in the mouse lymphoma cell line S49. We compared their mechanism of cellular entry and their potency to induce apoptosis through inhibition of de novo biosynthesis of phosphatidylcholine at the endoplasmic reticulum. Alkylphospholipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 33 publications
9
84
1
9
Order By: Relevance
“…Thus, we have found a positive correlation between perifosine uptake and NBD-aminophospholipid translocation (a wellestablished marker for aminophospholipid translocase activity) in several KB clones obtained in our laboratory. Furthermore, we found no correlation whatsoever between perifosine uptake and endocytosis rates in a subset of fourteen cell lines, which is in stark contrast with previous works where the role of raft-dependent endocytosis in perifosine uptake has been proposed [13,32,33]. This discrepancy 18 may, however, only be apparent if we consider that only adherent cell lines, but no leukemia or lymphoma cells, were used in the present study, whereas the authors who proposed the raft-dependent hypothesis for perifosine uptake have recently published a further study [15] where they discriminate between lymphoma and carcinoma cells on the basis of their prevalent perifosine-uptake mechanism (raftdependent endocytosis in the former, and a plasma membrane translocator in the latter).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, we have found a positive correlation between perifosine uptake and NBD-aminophospholipid translocation (a wellestablished marker for aminophospholipid translocase activity) in several KB clones obtained in our laboratory. Furthermore, we found no correlation whatsoever between perifosine uptake and endocytosis rates in a subset of fourteen cell lines, which is in stark contrast with previous works where the role of raft-dependent endocytosis in perifosine uptake has been proposed [13,32,33]. This discrepancy 18 may, however, only be apparent if we consider that only adherent cell lines, but no leukemia or lymphoma cells, were used in the present study, whereas the authors who proposed the raft-dependent hypothesis for perifosine uptake have recently published a further study [15] where they discriminate between lymphoma and carcinoma cells on the basis of their prevalent perifosine-uptake mechanism (raftdependent endocytosis in the former, and a plasma membrane translocator in the latter).…”
Section: Discussioncontrasting
confidence: 99%
“…However, some discrepancies have arisen concerning how perifosine enters cancer cells, and what previous steps are required for the drug to reach its intracellular targets and trigger cell death. Thus, it has been proposed that ALP enters cells either by raft-dependent endocytosis [13,32,33] or by transporter-mediated translocation of perifosine through the plasma membrane [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to targeting Akt and modulating JNK activation and DR5 expression, perifosine possesses other biologic activities (reviewed in [59]) that may contribute to the effects observed in this work. These include, accumulation into lipid rafts of the plasma membrane [60] and downregulation of ERK 1/2 phosphorylation [48]. Analysis of tumor xenografts revealed a strong reduction in ERK phosphorylation levels following perifosine treatment (data not shown), indicating that inhibition of MAPK signaling by perifosine toghether with Akt inhibition might also be involved in inducing tumor cells apoptosis and tumor growth delay.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have shown that perifosine accumulates in lipid rafts in a manner sensitive to raft disruption by cholesterol depletion (9)(10)(11). Subsequently, it was suggested that LFG, an anti-apoptotic protein with subcellular localization in lipid rafts, may interfere with perifosine-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%